Comparative efficacy of garlic (Allium sativum) and black cumin (Nigella sativa) as growth promoters in broilers - Jha, Prabhat; Singh, Namrata; Sah, Ramashish; Yadav, Jagat Lal; Jha, Shyam Shankar (Journal of Agriculture and Environment, 2014)
A study was conducted to determine the comparative effect of feeding different levels of garlic and black cumin on growth, feed consumption, feed efficiency and carcass characteristics of Hubbard broiler. Two hundred fifty two Hubbard chicks having uniform body weight were randomly allocated into seven dietary treatments with three replications .The isoproteinous and isocaloric formulated standard starter, grower, and finisher diets were supplemented for 6 weeks with different levels of freshly ground dry garlic and black cumin seeds in order of T1-control, T2- 0.25% garlic, T3- 0.5% garlic, T4- 0.75% garlic, T5- 0.25% black cumin, T6- 0.5% black cumin, and T7- 0.75% black cumin, respectively. The results showed significantly higher cumulative weekly live body weight, body weight gain and feed conversion ratio for broiler fed diet supplemented with 0.5% garlic, followed by diet supplemented with 0.5% black cumin. There was no significant effect of different levels of garlic and black cumin supplementation in diet on carcass characteristics. Furthermore, there was minimum gross expenditure in broiler diet supplemented with 0.25% garlic and maximum in broiler diet supplemented with 0.75% black cumin. However, there was highest gross income and net profit in broiler diet supplemented with 0.5% garlic, followed by broiler diet supplemented with 0.5% black cumin. It is therefore, concluded that inclusion of garlic or black cumin in the broiler rations may be used for economical and efficient production of broilers.